2020
DOI: 10.3390/su12114632
|View full text |Cite
|
Sign up to set email alerts
|

The Return on Investment in Social Farming: A Strategy for Sustainable Rural Development in Rural Catalonia

Abstract: Although social farming (SF) has been a successful endeavor in Catalonia over the last 30 years, it has not been visible for part of society, which is largely unaware of its existence. Nevertheless, this study has demonstrated after studying five cases that the social return on investment (SROI) has been significant in rural areas. In this study, five in-depth interviews were carried out, and a general questionnaire was sent to 161 SF projects in Catalonia with a view to analyzing the participation of stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
0
13
0
4
Order By: Relevance
“…Clients are not included in the outcomes since, following discussions with the company itself and based on similar studies (Tulla et al. 2020), clients experience a change in satisfaction after consuming the service received, and this measurement is outside the scope of this study. Moreover, in this particular case, clients are of a different nature due to the diversity of activities carried out by the company, which makes measuring the impact of this group more complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clients are not included in the outcomes since, following discussions with the company itself and based on similar studies (Tulla et al. 2020), clients experience a change in satisfaction after consuming the service received, and this measurement is outside the scope of this study. Moreover, in this particular case, clients are of a different nature due to the diversity of activities carried out by the company, which makes measuring the impact of this group more complex.…”
Section: Resultsmentioning
confidence: 99%
“…This includes the cost of salaries paid to workers with and without disabilities (from which the increase in family income would also be obtained due to the worker's contribution to the family economy, but this outcome is not accounted for numerically in order to avoid including any salary twice, thus opting for the most conservative option), the amount paid to suppliers, taxes paid to the Public Administration for certain accountable items, 2). Clients are not included in the outcomes since, following discussions with the company itself and based on similar studies (Tulla et al 2020), clients experience a change in satisfaction after consuming the service received, and this measurement is outside the scope of this study. Moreover, in this particular case, clients are of a different nature due to the diversity of activities carried out by the company, which makes measuring the impact of this group more complex.…”
Section: Monetize Outcomes and Adjustments (Phases 3 And 4)mentioning
confidence: 99%
“…También puede considerase que es una explotación de agricultura social (Tulla et al, 2020) aunque la empresaria agrícola no quiera reconocerlo por no menospreciar a sus empleados, aunque ello le impida obtener algunas ventajas económicas de la administración por emplear personas en riesgo de exclusión social.…”
Section: D) La Oportunidad Del Desarrollo Local Sostenibleunclassified
“…In Europe, the regulatory reference is in the programming cycle of the European Structural Funds 2014-2020 in the positions at the European level of achieving the SDG goals and in the objective of social inclusion and the fight against poverty (strategic objectives of the Europe 2030 Strategy). Despite the presence of many different activities and experiences, SF initiatives in Italy mainly aimed at the social and work inclusion of disadvantaged people, according to an inclusive approach [4,5,[16][17][18][19][20]. As argued by Moruzzo et al, 2020, while numerous benefits of social farming identified, the impact of social farming on the everyday lives of people with intellectual disabilities varies substantially [21].…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%